2018
DOI: 10.1038/s41586-018-0243-7
|View full text |Cite|
|
Sign up to set email alerts
|

Codon-specific translation reprogramming promotes resistance to targeted therapy

Abstract: Reprogramming of mRNA translation has a key role in cancer development and drug resistance . However, the molecular mechanisms that are involved in this process remain poorly understood. Wobble tRNA modifications are required for specific codon decoding during translation. Here we show, in humans, that the enzymes that catalyse modifications of wobble uridine 34 (U) tRNA (U enzymes) are key players of the protein synthesis rewiring that is induced by the transformation driven by the BRAF oncogene and by resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
214
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(220 citation statements)
references
References 33 publications
6
214
0
Order By: Relevance
“…Thus far, our data point out that regulation of mcm 5 s 2 ‐U34 tRNA‐modifying enzymes plays a major role in translational offsetting as a function of alterations in ERα signaling. Intriguingly however, ERα‐dependent suppression or decrease in the expression of U34‐modifying enzymes did not correlate with global changes in mcm 5 s 2 ‐U‐modified tRNAs as quantified by the [(N‐acryloylamino)phenyl]mercuric chloride (APM) method [Igloi, ; as reported in a recent study (Rapino et al , )] or mass spectrometry (Appendix Fig S6A and B). We reasoned that this may be a consequence of accumulation of modified tRNAs during chronic ERα depletion (e.g., due to reduction in global protein synthesis).…”
Section: Resultsmentioning
confidence: 96%
“…Thus far, our data point out that regulation of mcm 5 s 2 ‐U34 tRNA‐modifying enzymes plays a major role in translational offsetting as a function of alterations in ERα signaling. Intriguingly however, ERα‐dependent suppression or decrease in the expression of U34‐modifying enzymes did not correlate with global changes in mcm 5 s 2 ‐U‐modified tRNAs as quantified by the [(N‐acryloylamino)phenyl]mercuric chloride (APM) method [Igloi, ; as reported in a recent study (Rapino et al , )] or mass spectrometry (Appendix Fig S6A and B). We reasoned that this may be a consequence of accumulation of modified tRNAs during chronic ERα depletion (e.g., due to reduction in global protein synthesis).…”
Section: Resultsmentioning
confidence: 96%
“…The mechanisms that control this metabolic reprogramming by immediate changes in specific gene expression programs remain less clear. Now, an exciting new study by Rapino et al () provides evidence for an unexpected role of enzymes that modify transfer RNA (tRNA) in this process. Specifically, they show that enzymes modifying uridine 34 (U 34 ) of tRNA are important for the maintenance and therapeutic resistance of an aggressive skin cancer known as melanoma.…”
Section: Codon‐dependent Translation Regulation Of Hif1α Couples Glycmentioning
confidence: 99%
“…While U 34 tRNA‐modifying enzymes have been implicated in metabolism, DNA damage response, and exocytosis (Esberg et al , ; Begley et al , ; Laxman et al , ), their role in cancer has not been extensively studied until now. By employing a combination of approaches and patient samples, Rapino et al () demonstrate that key enzymes required for U 34 tRNA modifications are increased in melanomas exhibiting highly glycolytic phenotypes that are often associated with mutations in BRAF (one of the most commonly mutated genes in melanoma patients). Rapino and colleagues provide compelling evidence that BRAF V600E melanomas are “addicted” to high levels of U 34 tRNA‐modifying enzymes.…”
Section: Codon‐dependent Translation Regulation Of Hif1α Couples Glycmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, recent studies demonstrated that tRNA‐modifying enzymes can be implicated in disease. For example, a recent study provided evidence that certain wobble‐modifying enzymes are involved in resistance to cancer targeted therapy (Rapino et al , ). Since queuine is obtained from the diet, it will be interesting to determine whether Q deficiency or excess can result in disease.…”
Section: Dietary Queuine and Gut Microbiota‐derived Queuine Regulate mentioning
confidence: 99%